Evaluating growth and exploitation dynamics of Thunnus albacares for sustainable fisheries in fishery landed in Bali's Benoa Harbor - TRI DJOKO LELONO; GATUT BINTORO; ARIEF SETYANTO; DARMAWAN OCKTO SUTJIPTO; AGUS TUMULYADI; WIRASTIKA ADHIHAPSARI; WAHIDA KARTIKA SARI; MIHROBI KHALWATU RIHMI; DIAN ALIVIYANTI; ANDIK ISDIANTO; AGITA DWI ROSMALIA PUTRI (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Lelono TD, Bintoro G, Setyanto A, Sutjipto DO, Tumulyadi A, Adhihapsari W, Sari WK, Rihmi MK, Aliviyanti D, Isdianto A, Putri ADR. 2024. Evaluating growth and exploitation dynamics of Thunnus albacares for sustainable fisheries in fishery landed in Bali's Benoa Harbor. Biodiversitas 25: 2858-2869. This study aims to analyze the population dynamics of Thunnus albacares (Bonnaterre, 1788), particularly focusing on factors such as length-weight relationships, length frequency distribution, first caught size, gonadal maturity size, growth rate, mortality rate, and exploitation rate. The analysis, conducted using FISAT II software with data from 2018 to February 2022, also includes evaluating fish utilization status. This evaluation involves estimating Allowable Biological Effort (ABE), Allowable Biological Catch (ABC), and Total Allowable Catch (TAC) based on yellowfin tuna (T. albacares) production data from 2012 to 2021 in Bali’s Benoa Harbor. These parameters and analyses are crucial for maintaining the sustainability of catch utilization. This will be achieved using the Feedback Harvest Control Rules (FHCR) with a random sampling method. The length-weight relationship analysis yielded positive allometric growth (b>3), influenced by genetic, environmental, reproductive, and overexploitation factors. The initial catch size value (Lc50%) was determined to be 134.7 cmFL, while the gonadal maturity size (Lm) was estimated to be 103.3 cmFL. Therefore, it is paramount to refrain from fishing before reaching reproductive maturity to ensure the stock's survival. The asymptotic length (L?) was estimated at 235.45 cmFL, t0 -2.91, with a growth rate (K) of 0.20. This indicates a relatively slow growth rate, which is important information for effective fisheries management. The exploitation rate (E) of 0.88 per year indicates overexploitation. Hence, the need for sustainable fishing practices should be noted in certain areas. Applying the FHCR model provides insights into stock estimation and sustainable management strategies that are of value in informing the development of more careful management practices.